2020
DOI: 10.1007/jhep09(2020)113
|View full text |Cite
|
Sign up to set email alerts
|

Monopole and instanton effects in QCD

Abstract: We aim to show the effects of the magnetic monopoles and instantons in quantum chromodynamics (QCD) on observables; therefore, we introduce a monopole and anti-monopole pair in the QCD vacuum of a quenched SU(3) by applying the monopole creation operator to the vacuum. We calculate the eigenvalues and eigenvectors of the overlap Dirac operator that preserves the exact chiral symmetry in lattice gauge theory using these QCD vacua. We then investigate the effects of magnetic monopoles and instantons. First, we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 90 publications
1
22
0
Order By: Relevance
“…This Examining the effects of the finite lattice volume (left) and the discretization (right) on the fitting results of the slope AN I . The outcomes of β = 6.0000, V = 14 4 and β = 6.0522, V = 18 3 × 32 are reported in our previous research [39,41] shows that the numerical results are consistent with the prediction (5) and that the effects of the finite lattice volume are negligible.…”
Section: The Number Density Of the Instantons And Anti-instantons Of ...supporting
confidence: 76%
See 3 more Smart Citations
“…This Examining the effects of the finite lattice volume (left) and the discretization (right) on the fitting results of the slope AN I . The outcomes of β = 6.0000, V = 14 4 and β = 6.0522, V = 18 3 × 32 are reported in our previous research [39,41] shows that the numerical results are consistent with the prediction (5) and that the effects of the finite lattice volume are negligible.…”
Section: The Number Density Of the Instantons And Anti-instantons Of ...supporting
confidence: 76%
“…In the previous research [39,41], we found that the added monopole with a magnetic charge of +1 and antimonopole with a magnetic charge of -1 make one instanton or anti-instanton. The value of the chiral condensate, which is an order parameter of symmetry breaking, is defined as a negative number and decreases in direct proportion to the square root of the number density of the instantons and anti-instantons.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We compared the numerical results with the predictions and discovered the effects of the added monopole and anti-monopoles and the created instantons and anti-instantons on the observables as follows [16]:…”
Section: Introductionmentioning
confidence: 99%